A prospective randomized controlled trial on the comparative clinical efficiency and hygiene of a ceramic inter locking retainer and a flexible spiral wire bonded retainer - Abhishek Sinha; Saurabh Sonar; Puneet Batra; Sreevatsan Raghavan (Indian Journal of Dental Research, 2021)
Background: The lower canine to canine retainer is one of the most commonly used retention appliance. Objective: Compare and assess the clinical efficiency and oral hygiene maintenance with 2 retainers: flexible spiral wire and ceramic interlocking bonded. Setting and Sample Population: Orthodontic department of a dental college. Participants, Study Design and Methods: Prospective randomized controlled trial that involved 40 patients who had completed orthodontic treatment and were randomly allotted to either group: flexible spiral wire (FSW) or ceramic interlocking retainers. Allocation ratio was 1:1. Eligibility Criteria: Completed fixed orthodontic treatment with an acceptable treatment result. Main Outcomes: Oral hygiene was assessed at 3 (T1) and 6 (T2) months intervals after debonding using Gingival and Plaque index. The contact point displacement was assessed using 3D model superimposition and bonded retainer failure was noted. Randomization and Blinding: Computer-generated random allocation, only data analyzer was blinded. Statistics: Data normality was tested using the Shapiro-Wilk and Q-Q plot. Mixed model analysis was used to assess differences between the two groups for the above-mentioned parameters. The failure rate of the retainer was calculated by the Chi-Square test. Results: Only the plaque index score was significantly greater in the FSW group and showed a statistically significant difference (P < 0.05), rest of the parameters showed no statistically significant difference over the specified time points, although a mild increase in relapse was noted in both groups No serious harms were reported. Conclusion: Both retainers seem to be effective in maintaining the treatment results however the FSW seems to accumulate more plaque over a given period of time thereby mandating proper hygiene maintenance and follow-up.